Relationships between growth mindsets and math achievement across socioeconomic status in 74 countries: Evidence from PISA 2022 - Pimmada Charoensilp; Hanjoe Kim; Suppanut Sriutaisuk (PLoS ONE, 2025)
Growth mindsets have gained attention from education stakeholders due to their potential to enhance academic outcomes. However, some studies found that the relationship between mindsets and student achievement varied by socioeconomic status, while others found no association. As a result, it remains unclear whether growth mindsets are more beneficial for students from higher- or lower-socioeconomic backgrounds, or whether their benefits are consistent across all socioeconomic groups. This paper aims to investigate the moderating role of socioeconomic status in the relationship between growth mindsets and math achievement among 15-year-old students, using data from PISA 2022, which includes 507,588 representative students from 74 countries. The results showed that growth mindsets were significantly and positively related to achievement beyond socioeconomic status in the majority of countries. However, the moderating role of socioeconomic status varied across countries, with no consistent pattern emerging. These findings underscore the importance of considering contextual and cultural factors when promoting growth mindsets, as their benefits for math achievement may differ depending on students’ socioeconomic backgrounds and the educational environments in which they are situated.